Manajemen Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru di SMKS Mahyal Ulum Al-Aziziyah - Daman Huri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to describe and examine more deeply how the principal's management improves teacher professionalism at SMKS Mahyal Ulum Al-Aziziyah. Success in education can be measured from various aspects, but the main factor that most influences is the principal as the leader responsible for the educational process. This research uses a qualitative approach with a case study design. Data sources were obtained through principals and teachers using observation, interview, and documentation data collection techniques. Data were analyzed through data reduction, data presentation, and conclusion drawing. The research findings indicate that principal management at SMKS Mahyal Ulum consists of planning, implementation, supervision, and organizing. The principal plays roles as an educator, manager, supervisor, motivator, and innovator. Management steps include conducting supervision, providing rewards, motivating, and encouraging continued education. Supporting factors for principal management in improving teacher professionalism include the fulfillment of teaching staff, discipline, motivation, and a conducive environment. The inhibiting factors are the limited number of certified honorary teachers, time management of teachers and staff, and lack of understanding of information technology.Â